Estudio de la Variabilidad Genética en poblaciones naturales de Sacha Inchi Plukenetia Volubilis L. (Euphorbiaceae) de la región San Martín - Corazon Guivin, Mike Anderson (2009)
In the Amazon area, the Euphorbiacea family is constituted by species of great economic importance such as sacha inchi Plukenetia volubilis L. (Linnaeus, 1753) Currently this species has been investigated concerning culture, but there is little about its genetic information, especially in natural populations. In this regard the present investigation tries to contribute to the knowledge of the genetic variability of sacha inchi in natural populations of the San Martín region. These populations were evaluated by means of the molecular technique DALP. A total of 83 samples collected in the localities of Havana (21), Shica (20), Cerro Alto (21) and Tununtunumba (21) was analyzed with the technique DALP “Direct Amplification of Length of Polymorphism”. From eight DALP markers used, three turned out to be informative (DALP221, DALP233 y DALP242), showing differences at an intra and inter-population level. The results of the AFC, index of fixation (average of Fst = 0.82) and genetic distance (average of D = 2.56) show that the four populations form independent genetic organizations. This could be attributed to the mixed pollinization system (autogamy and allogamy) present in this species. That would be acting preferably only between the individuals of each population, but not between different populations. At an intrapopulation level the population of Shica has the greatest genetic diversity (15 genotypes) of the four studied populations, which would be related to the great size and population density. This would favor the cross- fertilization, having as a consequence a greater genetic diversity. The high genetic diversity between the four populations of this species could be due to the absence of direct pollinizer insects as well as the presence of natural barriers and the geographic distance between them, which would be restricting the gene flow between the populations.